2011
DOI: 10.1364/ol.36.002922
|View full text |Cite
|
Sign up to set email alerts
|

Realization of single-mode telluride rib waveguides for mid-IR applications between 10 and 20 μm

Abstract: The feasibility of all-telluride integrated optics devices based on waveguides presenting a single-mode behavior in the spectral range (10-20 μm) is demonstrated. These waveguides are constituted of a several micrometer thick Te(82)Ge(18) film deposited onto a Te(75)Ge(15)Ga(10) bulk glass substrate by thermal coevaporation and further etched by reactive ion etching under the CHF(3)/O(2)/Ar atmosphere. The obtained structures were proven to behave as channel waveguides with a good single-mode transmission over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…Moreover this new component had a higher transmission than the previous ones. Indeed the overall transmission varied between 3.5% and 4.5% over the 10-20 lm range for the best previous components [10], whereas an average transmission of 6% was observed in the buried channel waveguides, with a value of 9% at k = 10 lm, as mentioned above.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Moreover this new component had a higher transmission than the previous ones. Indeed the overall transmission varied between 3.5% and 4.5% over the 10-20 lm range for the best previous components [10], whereas an average transmission of 6% was observed in the buried channel waveguides, with a value of 9% at k = 10 lm, as mentioned above.…”
Section: Discussionsupporting
confidence: 51%
“…Rib waveguides lie at the surface of the components and are not buried under a superstrate. We found that two rib waveguides were necessary to cover the whole 6-20 lm spectral range: a narrow rib waveguide, single-mode from 6 to 11 lm and a larger one being single-mode from 10 to 20 lm [10][11][12]. In the present paper, the design of a new alltelluride buried waveguide, able to cover the whole spectral range from 6 to 20 lm is presented.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…A range of chalcogenide compositions have been explored for phase change memory devices [7] and crystalline GeTe 4 was reported to be a promising phase change memory material due to its good thermal stability and low power consumption [8]. Recently GeTe 4 rib waveguides were explored in the mid-IR range of 6-20 µm for spatial interferometry in the search for earthlike planets, where the index contrast between the GeTe 4 core and the Te 75 Ge 15 Ga 10 substrate was about 4 x 10 -2 [9][10][11]. In this paper, we describe the fabrication of a "high contrast" (Δn ≈ 1), GeTe 4 single mode rib waveguide on a ZnSe substrate, transmitting over the spectral range from 2μm -20µm.…”
Section: Introductionmentioning
confidence: 99%